Customer-Based Brand Equity for Branded Apps: A Simple Research Framework. Issue 5 (4th July 2021) - Stocchi, Lara; Ludwichowska, Gosia; Fuller, Rachel; Gregoric, Anna
ABSTRACT: The purpose of this study is to understand how to build strong branded mobile applications, i.e. apps inherently displaying a brand identity. This is pursued by outlining and testing a simple Customer-Based Brand Equity (CBBE) framework, adapted from the latest advances in conceptualisation and measurement of a brand's intangible value from a consumer perspective. In more detail, this study introduces a series of measures capturing a branded app's awareness and a key component of a branded app's image – i.e., brand-attribute associations that make the app 'mentally available', or simply more likely to come to mind when deciding which app to download and/or use. These measures are then linked to market penetration to infer the overall strength or equity of a branded app. They are also considered in relation to app stickiness by comparing results for current users of the app vs. non-users of the app. The empirical outcomes of this study highlight that strong branded apps are simultaneously easy to recognise and mentally available. These two factors underpin market penetration within a given category of apps irrespective of stickiness. Combined, these findings advance research on mobile apps and provide guidelines for the strategic management of branded apps that are independent of stores' rankings.